Patterns and Predictors of Premenstrual Symptoms among Females Working in a Psychiatry Hospital - Sunita Kumari; Ankur Sachdeva (Scientifica)
Introduction. Premenstrual syndrome presents with vague psychological, somatic, or biological symptoms. It may be seen more commonly in a specific profile of patients. We try to evaluate the patterns and predictors of premenstrual symptoms among females working in a tertiary care psychiatry hospital. Methodology. We recruited working females at a tertiary care psychiatry hospital in India, through purposive sampling, and assessed them cross-sectionally. Premenstrual Symptom Checklist was used to assess the frequency and distribution of premenstrual symptoms, which were correlated with various sociodemographic variables to evaluate the predictors for premenstrual symptoms. Results. 150 working females were included, belonging to different sociodemographic profile. Somatic symptoms (backache, joint and muscles pain, and fatiguability) were most commonly reported followed by psychological (irritability and losing temper easily) and biological symptoms (increased micturition). Premenstrual symptoms were seen more commonly in women with higher educational status and nursing profession and residing in nuclear families (p<0.05), while age and marital status did not correlate significantly. Discussion. Premenstrual symptoms are common and distressing, especially for working females. Somatic symptoms such as backache and joint pains predominate over psychobiological symptoms. Women with higher educational status and professions like nursing belonging to nuclear families are more prone to these symptoms. Attention needs to be given to premenstrual symptoms in such population of working females.